MOVE ANALYSIS OF HIGHLY CITED SCOPUS ENGLISH LANGUAGE TEACHING JOURNAL ARTICLES - Fuji Nurizka Amalia; Eri Kurniawan (Indonesian EFL Journal, 2025)
Producing quality research articles requires researchers to have a comprehensive understanding of move analysis, a structural approach that uses moves and steps to effectively present arguments and findings. Despite extensive research on move analysis structures, there remains a gap in frameworks addressing the move-step structures across all sections of highly cited research articles, particularly in the field of English Language Teaching (ELT). This study seeks to fill this gap by analyzing the structural patterns of move-step sequences in ELT research articles, providing a practical framework for novice researchers. Employing a multi-framework approach, Hyland's (2000) model was used for Abstracts, Swales' (2004) for Introductions, Cotos' (2017) for Methods, and Moreno and Swales' (2018) for Results and Discussion sections. A corpus of 30 highly cited ELT research articles indexed in Scopus was analyzed. The findings reveal that specific moves, such as presenting background, reporting the research method and results are consistent across Abstracts, and topic generalization, indicating a gap, and announcing present research across Introductions. Similarly, the Method sections exhibit two dominant moves: contextualizing study methods and describing the study, while the Results and Discussion sections highlight four key moves, including reporting background information, presenting and highlighting results, and interpreting and explaining results. This research underscores the importance of recognizing conventional and optional moves in crafting high-quality articles. The proposed framework is expected to serve as a comprehensive guide for novice researchers in producing impactful and well-structured ELT research articles, contributing to the field's scholarly discourse.Keywords: ELT research article; move analysis; research framework